العلاقة بين القراءات القرآنية ووجوه اللغة العربية عند ابن سيده في كتابه "المحكم والمحيط الأعظم": The relationships between the Qur’ani readings and aspects of the Arabic language according to Ibn Sayyidah in his book "Al-Hakam wa Al-Mohet Al-Aazam" - Salman Bukhari; Nashwan Abdu Khalid (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2022)
ملخص تعتبر القراءات القرآنية سواء المتواترة منها أو الشاذة من المصادر الأصيلة في علم اللغة العربية، لذا تناول هذا البحث بيان حقيقة هذه المصدرية، وعلاقة الوجوه اللغوية بين الظواهر الصرفية والصوتية والنحوية التي استعملتها العرب قديمًا في لهجاتهم، وبين ما جاء بها القرآن بقراءاته المتنوعة لوصف تلك الظواهر اللغوية المنتشرة بين القبائل، وصحة الاستشهاد بها؛ لأن القرآن نزل بلغتهم، مع بيان استشهاد علماء اللغة بالقراءات على بناء قواعدهم، وبخاصَّة صُنَّاع المعاجم الذين وظَّفوا القراءات القرآنية بوصفها شواهد على مسائل اللغة، ويأتي ابن سيده في مقدمتهم، حيث هدف البحث إلى بيان مسلك ابن سيده في إعمال القراءة كشاهد من شواهد اللغة، ومعرفة دور القراءات في حفظ لغات العرب وأوجه كلامها، وتأثيرها البالغ في معرفة الفصيح من الأفصح من خلال النماذج التطبيقية المنتخبة من الكتاب، وإبراز تلك الأوجه في ثراء اللغة بها من حيث اللفظ والمعنى، وقد سار هذا البحث على المنهج الوصفي والتحليلي، حيث ركَّز على المواضع في الآيات القرآنية التي استشهد بها ابن سيده على أهمية القراءات في معرفة بعض اللهجات العربية، ودورها في حفظ تلك اللغات، والعلاقة الوثيقة بينهما، وقد توصَّل البحث إلى عدة نتائج من أهمها: أن القراءات القرآنية حفظت اللغة العربية من الضياع والاندثار؛ لأن الله تعالى تكفَّل بحفظ سائر الأحرف القرآنية التي أنزلها، والأحرف القرآنية احتوت على خلاصة ما في لغات القبائل العربية من فصيح الألفاظ والتراكيب والأساليب واللهجات، فكان بذلك مرجعًا قطعيًا لا يتطرق عليه شك، كما أنه ينبغي الاعتماد على القراءات القرآنية متواترها وشاذِّها في دراسة العربية الفصحى؛ لأن روايات هذه القراءات تُعَدُّ أوثق الشواهد التي تُبَيِّنُ اللغة على ما كانت عليه ظواهرها الصوتية والصرفية والنّحوية، وغيره من النتائج التي ضمنها هذا البحث في الخاتمة. Abstract This study aimed mainly at Qur’anic readings, whether frequent or unnatural ones are considered among orginal sources in Arabic linguistics, Therefore, this research deals with the statement of the truth of this source, and the relationship of linguistic faces between the morphological, phonetic and grammatical phenomena that the Arabs used in the past in their dialects. And what the Qur’an came with in its various readings to describe those linguistic phenomena that are widespread among the tribes, and the validity of citing it, if the Qur’an was revealed in their language. With the statement that linguists cite the readings on the construction of their grammer, especially the lexicographers who used the Qur’anic readings as evidence on language issues. Ibn Sayyidah comes in their introduction, where the aim of the study is to explain the behavior of Ibn Sayyidah in the realization of reading as a testament to the language. Knowing the role of reading in memorizing the language of Arabs and the aspects of speec, and its impact on knowledge of eloquent from the eloquent through the applied models selected from the book, and to hightlight these aspects in the richness of the language in terms of pronounciation and meaning where this reaseach has followed the descriptive and analytical method. Where he focused on the places in the Qur’anic verses cited by Ibn Sayyidah on the importance of readings in knowledge of some Arab dialects, and their role in preserving those languages. And the close relationship between them, and the reseach reached several results, the most important of which are: The Qur’anic readings preserved the Arabic language from loss and extinction; Because Allah Almighty ensured the preservation of all the Qur’anic letters that He revealed, which also contains a summary of what is in the language of the Arab tribes of eloquent words, structures, styles and dialects. Thus, it was definitive reference that is beyond doubt and it necessary to rely on the frequent and unnatural readings in the classical Arab study, because the narrations of these readings are considerd the most reliable evidence that shows the language as its phonetic, morphological, and grammatical phenomena and other results included in the conclusion.